When the rule of law and constitutionalism become a mirage : an analysis of constitutionalism and the rule of law in post-independent Cameroon against post-apartheid South Africa - Van Marle, Karin (University of Pretoria, 2016)
Thesis (LLD)--University of Pretoria, 2015.